2016
DOI: 10.4236/ce.2016.76093
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Academic Staff and Students towards the Objective Structured Clinical Examination (OSCE) in Obstetrics and Gynaecology

Abstract: Introduction: The Department of Obstetrics and Gynaecology first implemented the Objective Structured Clinical Examination (OSCE) in the final examinations in 2003 academic year to replace the long case and oral examination on short cases and to evaluate the attitude of staff and medical students towards OSCE as a method of clinical assessment. Methods: Three main groups were evaluated: 1) 96 medical students at their final examination in Obstetrics and Gynaecology and were assessed with OSCE; 2) 30 Kuwait tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…The majority of the students (66.7%) reported that they needed more time at stations whereas examiners felt that the time at stations was adequate (59.1%). A similar difference of opinion was also observed between students (41.7%) and examiners (11.1%) in a study conducted by Omu et al11 in Kuwait. Some studies have raised concerns that time was a problem and suggested that they focus on restricting time but rather should concentrate on how well students can perform 38,39.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The majority of the students (66.7%) reported that they needed more time at stations whereas examiners felt that the time at stations was adequate (59.1%). A similar difference of opinion was also observed between students (41.7%) and examiners (11.1%) in a study conducted by Omu et al11 in Kuwait. Some studies have raised concerns that time was a problem and suggested that they focus on restricting time but rather should concentrate on how well students can perform 38,39.…”
Section: Discussionsupporting
confidence: 82%
“…In both campuses, students expressed some concerns regarding OSCE, e.g., stressful and intimidating event and insufficient time to complete the stations. Similar acceptance and concerns of the OSCE have been previously described by the students in other medical schools worldwide 11,12,28,29…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This supports the fact that OSCE is a fairer assessment tool. [ 7 13 22 ] The low reliability of the traditional clinical examination meant a significant variation between individual student's score in long and short cases. The student's scores is not consistently low or high as the case might be.…”
Section: Discussionmentioning
confidence: 99%